2023
DOI: 10.3390/ijms24076399
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Ferroptosis-Related Genes in the Peripheral Blood of Patients with Relapsing-Remitting Multiple Sclerosis and Its Diagnostic Value

Abstract: Multiple sclerosis (MS) is a neurodegenerative disease with a complex pathogenesis. Re-lapsing-remitting multiple sclerosis (RRMS) is the most common subset of MS, accounting for approximately 85% of cases. Recent studies have shown that ferroptosis may contribute to the progression of RRMS, but the underlying mechanism remains to be elucidated. Herein, this study intended to explore the molecular network of ferroptosis associated with RRMS and establish a predictive model for efficacy diagnosis. Firstly, RRMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Most of the studies related to MS pathology were performed in the EAE model, animal model of MS and several types of cell models. In humans, bioinformatic analyses of ferroptosis genes in the pre-existing transcriptome datasets predominate [ 13 , 14 ]. There is a lack of studies conducted in MS patients encompassing clinical features and disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies related to MS pathology were performed in the EAE model, animal model of MS and several types of cell models. In humans, bioinformatic analyses of ferroptosis genes in the pre-existing transcriptome datasets predominate [ 13 , 14 ]. There is a lack of studies conducted in MS patients encompassing clinical features and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ferroptosis-related gene expression signatures to define the set of genes whose differential expression could reflect MS severity or distinguish extreme disease phenotypes, mild relapse–remitting (RR) MS and severe secondary progressive (SP) MS, have not been identified yet. Recent efforts have been made to suggest the enrichment of biological functions associated with ferroptosis, by reanalyzing the existing transcriptome data sets in MS [ 13 , 14 ]. Targeted sequencing of the particular pathway and its close regulators may provide higher sensitivity for detecting both low-abundant and less variable transcripts that could be missed by a transcriptome analysis approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a key requirement for mobilizing redox active iron for ferroptosis is present in CH-EAE and SPMS. A recent study screening ferroptosis related genes in peripheral blood of RRMS cases reported down-regulation of NCOA4 [ 67 ]. This may indicate protection and promotion of remission in RRMS by preventing release of redox active iron from ferritin stores.…”
Section: Discussionmentioning
confidence: 99%